2016
DOI: 10.1097/md.0000000000005531
|View full text |Cite
|
Sign up to set email alerts
|

Vitreous lavage fluid and bronchoalveolar lavage fluid have equal diagnostic value in sarcoidosis

Abstract: Here, we elucidate the immunological features of both bronchoalveolar lavage fluid (BALF) and vitreous lavage fluid (VLF) samples from patients with histopathologically verified sarcoidosis. In addition, we assess the safety of vitrectomy in sarcoidosis patients by investigating the occurrence of complications and the recovery of visual acuity.Twenty-two eyes of 22 patients with tissue-proven sarcoidosis were enrolled in this study. BALF and VLF samples were obtained and compared in each patient, and the clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“… 1 In our previous study, we reported finding similar CD4/CD8 ratios between the vitreous and the bronchoalveolar lavage fluid in patients with sarcoidosis. 22 Therefore, these findings suggest that the CD4/CD8 ratio in the vitreous fluid has predictive value for diagnosing sarcoidosis. If a patient is suspected of having sarcoidosis based on vitreous sample examination, it is then necessary to perform further clinical observations and treatments.…”
Section: Discussionmentioning
confidence: 76%
“… 1 In our previous study, we reported finding similar CD4/CD8 ratios between the vitreous and the bronchoalveolar lavage fluid in patients with sarcoidosis. 22 Therefore, these findings suggest that the CD4/CD8 ratio in the vitreous fluid has predictive value for diagnosing sarcoidosis. If a patient is suspected of having sarcoidosis based on vitreous sample examination, it is then necessary to perform further clinical observations and treatments.…”
Section: Discussionmentioning
confidence: 76%
“…100 Only one of these patients with a normal chest X-ray had a chest CT. Two studies reported that CD4 þ/CD8þ ratios of vitreous lymphocytes were significantly higher in sarcoid uveitis versus other forms of uveitis. 101,102 The sensitivity and specificity of the vitreous CD4 þ/CD8þ ratio were 100 and 96.3%, respectively, for the diagnosis of intraocular sarcoidosis, suggesting a diagnostic value comparable to that of the CD4 þ/CD8þ ratio in BAL fluid for pulmonary sarcoidosis. 101 However, measurement of the vitreous CD4 þ/CD8þ ratio is a challenging investigation and the majority of panel members involved in the revision of the IWOS criteria considered this test to be too invasive to be performed solely for the purpose of diagnosing ocular sarcoidosis.…”
Section: New Diagnostic Toolsmentioning
confidence: 96%
“…Vitreous CD4/CD8 ratio >3.5 has been shown to be comparable to CD4/CD8 ratio in bronchoalveolar lavage (BAL) fluid for pulmonary sarcoidosis 91,92 . Vitreous CD4/CD8 ratio has been shown to have a sensitivity of 100% and specificity of 96.3% 91,92 .…”
Section: Ocular Investigationsmentioning
confidence: 99%